Конституція УНР 1918 року: історія розробки, прийняття та оцінки в історіографії - Логвиненко, І. А.; Lohvynenko, I. A.; Логвиненко Ігор Альбертович (Право і безпека. – 2017. – № 1 (64). – С. 35-39, 2017)
Досліджено основні етапи конституційного процесу в Україні у період існування Української Центральної Ради. Висвітлено історію розробки та прийняття Конституції Української Народної Республіки. Проаналізовано її зміст. Показано розходження науковців в оцінках Основного Закону УНР, що пояснюється різними підходами та критеріями до визначення її сутності та значення. Зроблено висновок, що, хоча Конституція УНР була прийнята в останній день існування Центральної Ради і не діяла жодного дня, це не може применшити її значення в історії вітчизняного революційного конституціоналізму. Текст Основного Закону не тільки враховував найкращі досягнення світової та національно-правової думки, а й за рівнем демократичності багато в чому і перевищував усі сучасні йому конституції. Не поступався він чинним тоді основним законам і за рівнем правової культури та юридичної техніки.

The main stages of the constitutional process in Ukraine in the period of the Ukrainian Central Rada have been studied. The history of the development and adoption of the Constitution of Ukrainian People’s Republic has been highlighted. Its content has been analyzed. The author has demonstrated the differences in scholars’ estimations of the Basic Law of UPR that is explained by different approaches and criteria to determine its nature and significance. It has been concluded that although the Constitution of UPR was adopted on the last day of existence of the Central Rada and did not act any single day, it can not diminish its significance in the history of the national revolutionary constitutionalism. The text of the Basic Law not only took into account the best achievements of the world and national and legal thought, but according to the level of democracy exceeded all contemporary constitutions in many aspects. It was not worse than the current the Basic Laws by the level of legal culture and legal technology. Having established the democracy through the legislative agency and declared a parliamentary republic with democratic governments (three branches) and management, the Constitution provided the features of a legal state to UPR. As the current Constitution of Ukraine, the Basic Law of 1918 also declared the territory of Ukrainian People’s Republic as united and integral. Development and adoption of the Constitution of UPR were important stages in Ukrainian constitutionalism, which created the basis for future legislative activity.

Исследованы основные этапы конституционного процесса в Украине периода Центральной Рады. Раскрыта история подготовки и принятия Конституции Украинской Народной Республики. Проанализировано её содержание. Показаны расхождения исследователей в оценках Основного Закона УНР, что объясняется разными подходами и критериями к определению её сущности и значения. Сделан вывод, что, хотя Конституция УНР была принята в последний день существования Центральной Рады и не стала действующей, это не может уменьшить её значение в истории отечественного революционного конституционализма. Текст Основного Закона не только учитывал лучшие достижения мировой и национально-правовой мысли, но и по уровню демократичности во многом превосходил все конституции того времени. Не уступал он и по уровню правовой культуры и юридической техники.
Конституция УНР 1918 года: история разработки, принятия и оценки в историографии
The Constitution of Ukrainian people’s Republic of 1918: history of development, adoption and assessment in the historiography
Keywords: Конституційне право. Constitutional Law. Конституционное право; Держава і право. State and Law. Государство и право; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; Конституція; Історія. History. История; Українська Центральна Рада; Українська Народна Республіка; історіографія; універсал; Конституційна комісія; Основний Закон; автономія; федерація; незалежність; суверенність; Constitution; Ukrainian Central Rada; Ukrainian People’s Republic; historiography; Universal; Constitutional Commission; Basic Law; autonomy; federation; independence; sovereignty; Конституция; Украинская Центральная Рада; Украинская Народная Республика; историография; универсал; Конституционная комиссия; Основной Закон; автономия; федерация; независимость; суверенитет; Конституція УНР 1918 р.